SIFAT DASAR KAYU JATI PLUS PERHUTANI DARI BERBAGAI UMUR DAN KAITANNYA DENGAN SIFAT DAN KUALITAS PENGERINGAN - Efrida Basri; Imam Wahyudi (BRIN Publishing, 2013)
Jati Plus Perhutani (JPP) is a fast growing trak (Icctona grandis 1.f.) species that bas been developed since 20 years ago iry Research and Development Center of Perum Perhutani through a serial program of tree improvement. At the same age, stem diameter ameter of this superior trak tree is larger than that of the conventional trak. However, wood behavior during kiln drying bas net been much studied. This study excaminad drying property and quality of 5,7 and 9 year old of JPP woods in relation to their wood basic properties. Results showed that basic properties of JPP wood are inferior compared than those of conventional trak wood. Drying property and quality are affected significantly by cell wall thickness, juvenile wood portion, heartwood-tapwood percentage, MEA, initial moisture content, wood density and specific gravity, as well as growth stresies. Compared to those of conventional teak wood with similar in diameter (ulder tree), drying quality of JPP wood until 9 year-old was still poor and unfavorable. Based on the drying, quality and specific condition of the PP wood, the minimum maccimum drying temperature aus around of 30-40°C for 5 yarald, 40-50°C for 7 year old and-40-600°C for 9 year old.